Detection of spontaneous CD4+ T-cell responses in melanoma patients against a tyrosinase-related protein-2-derived epitope identified in HLA-DRB1*0301 transgenic mice - Paschen, Annette; Song, Mingxia; Osen, Wolfram; Nguyen, Xuan-Duc; Schadendorf, Dirk (Clinical cancer research, 2005)
Purpose: The frequently expressed differentiation antigen tyrosinase-related protein-2 (TRP-2) has repeatedly been described as a target of spontaneous cytotoxic T-cell responses in melanoma patients, suggesting that it might be an ideal candidate antigen for T cell-based immunotherapy. As a prerequisite for immunization, T-cell epitopes have to be identified. Whereas a number of HLA class I-presented TRP-2-derived epitopes are known, information about HLA class II-presented antigenic ligands recognized by CD4+ T helper (Th) cells is limited. - Experimental Design: The search for TRP-2-derived Th epitopes was carried out by competitive in vitro peptide binding studies with predicted HLA-DRB1*0301 ligands in combination with peptide and protein immunizations of HLA-DRB1*0301 transgenic mice. In vivo selected candidate epitopes were subsequently verified for their immunogenicity in human T-cell cultures. - Results: This strategy led to the characterization of TRP-260-74 as an HLA-DRB1*0301-restricted Th epitope. Importantly, TRP-260-74-reactive human CD4+ Th cell lines, specifically recognizing target cells loaded with recombinant TRP-2 protein, could be established by repeated peptide stimulation of peripheral blood lymphocytes from several HLA-DRB1*03+ melanoma patients. Even short-term peptide stimulation of patients' peripheral blood lymphocytes showed the presence of TRP-260-74-reactive T cells, suggesting that these T cells were already activated in vivo. - Conclusion: Peptide TRP-260-74 might be a useful tool for the improvement of immunotherapy and immune monitoring of melanoma patients.